Pendanaan Pendidikan Di Indonesia - Syakdiah, Syakdiah (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2005)
Education is universal basic human need. The Indonesian state founder also realize that matter Hence "educating the nation" representing one of the target of state founding. In the constitution it is aim mentioned that each citizen entitled to get the education. But in Indonesia development history , education sector always pulled over and get less attention. This is can be seen from the proportion of education sector in APBN ID. The implementation of education decentralization on the chance of will upgrade and amenity access, but in the practically not such as those which expected. That happened exactly with privatiszation and education commercialization, so that education expense become costly. As a result a lot of school age child have no access go to the school because unable to pay education expense.